Analysis of reactivity pattern of venereal disease research laboratory test in a tertiary care hospital - P., Prabahar; C., Vijayabhaskar (International Journal of Research in Medical Sciences, 2017)
Background: In India, sexually transmitted diseases are one of the major risk factors for acquisition of HIV and infertility. Most of the sexually transmitted diseases are asymptomatic and we rely on cytology, culture, serological evidence and sexual history to diagnose them. VDRL and TPHA are the two most important serological tests in the diagnosis of syphilis. Aim of the study was analysis of quantitative VDRL reactivity pattern and the prevalence of false positive VDRL. Methods: 7543 patient records were taken. Age, gender, and referral status were recorded. Total records of study population were divided into 2 groups. Group 1- true positive-both VDRL and TPHA Positive. Group II- False positive- VDRL positive and TPHA negative. Results: Among 7543 cases the ratio of True positive: false positive = 84:16 and in both groups males outnumbered females. In both groups, low titer VDRL took 70%. 61% of false positive cases were in the older age group. Conclusions: True positives were seen mainly in younger sexually active age group with majority having low titer VDRL (Less than 1:8) emphasizing the need for creating awareness of STDs among this age group and the need for early interventions.